A literature review on the European Super League of football – tracing the discussion of a utopia?. Issue 3 (3rd July 2022) - Macedo, Anthony; Ferreira Dias, Marta; Mourão, Paulo Reis
ABSTRACT: For football, 2021 will be marked as the year in which a European Super League (ESL) came closer than ever before to becoming a reality. Nonetheless, one can find many mentions of the ESL in men's football in studies published over the last decades (192 studies collected from Google Scholar), making this an appropriate time to conduct a literature review. Because the year 2021 could represent a turning point for the theoretical conception, the possible formats and features, and the main problems associated with the ESL, it will be interesting to compare past and present research with literature published later. This review highlights the main perspectives of discussion in the literature and points to some gaps, such as the tendency to overlook leagues outside the big five and grassroots. Moreover, the determinants of stadium attendance and TV audience for current competitions are generally transposed to an ESL without considering the potential impact of changing traditional habits and rivalries. Therefore, this study is expected to establish a baseline for future research and policies in the context of European football.